2013
DOI: 10.1063/1.4812318
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching with self-rectifying behavior in Cu/SiOx/Si structure fabricated by plasma-oxidation

Abstract: We report a resistive switching memory structure based on silicon wafers by employing both materials and processing fully compatible with complementary metal-oxide semiconductor technology. A SiOx nanolayer was fabricated by direct plasma-oxidation of silicon wafers at room-temperature. Resistive switching behaviors were investigated on both p- and n-Si wafers, whereas self-rectifying effect was obtained in the Cu/SiOx/n-Si structure at low-resistance state. The self-rectifying effect was explained by formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
1
22
1
Order By: Relevance
“…4(d), Φ B,eff is calculated to be 0.5 eV with fitting slope is ∼−0.28. The Shottky barrier height between Cu and n type silicon in our work is different from previous reported works (0.4 eV 23 or 0.6 eV 44 ), and fabrication and measurement could have effect on the practical status of metal-semiconductor contact surface, 23 and then influence the Φ B,eff . On this account, it's reasonable that there are deviations for Schottky barrier heights between the same contact materials, and this also afford us an effective way to attain high rectification ratio through optimizing and controlling the fabrication process.…”
Section: -7contrasting
confidence: 49%
See 2 more Smart Citations
“…4(d), Φ B,eff is calculated to be 0.5 eV with fitting slope is ∼−0.28. The Shottky barrier height between Cu and n type silicon in our work is different from previous reported works (0.4 eV 23 or 0.6 eV 44 ), and fabrication and measurement could have effect on the practical status of metal-semiconductor contact surface, 23 and then influence the Φ B,eff . On this account, it's reasonable that there are deviations for Schottky barrier heights between the same contact materials, and this also afford us an effective way to attain high rectification ratio through optimizing and controlling the fabrication process.…”
Section: -7contrasting
confidence: 49%
“…On this occasion, the average and worst OFF/ON ratios are calculated to be ∼10 4 and ∼130, respectively. In terms of rectification ratio, the average value is ∼10 4 and the minimum one is ∼370 when |V read | sets as 1 V. Therefore, it can be concluded that our Cu/HfO 2 /n-Si RRAMs are equipped with superior performance with higher OFF/ON and rectification ratios than previously reported self-rectifying RRAMs, 17,[21][22][23][24]30 thus suggesting a more promising prospect in future application.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, the selfrectifying effect in n-oxide/p-Si and p-oxide/n-Si structures can solve the cross talk interference due to sneak current [2][3][4]. Another simple method for realizing selfrectifying switching behavior is taking advantage of the Schottky barrier between the formed oxygen vacancy filament and semiconducting electrode in Pt/TaO x /n-Si [5] and Cu/SiO x /n-Si [6]. Similarly, it is an appropriate routine to suppress the sneak current in a metal/p-oxide/n-oxide/metal device simultaneously containing resistive switching and diode effect.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, the shape of the silicon bottom electrode (BE) can be easily modified by using an anisotropic wet etching process, which provides better resistive switching performance [21,22]. Also, a self-rectifying resistive characteristic is obtained by adjusting the doping concentration, which is one of the strongest advantages in a high-density crossbar array [23][24][25]. However, the resistive switching characteristics depending on dopant concentration still lack investigation.…”
Section: Introductionmentioning
confidence: 99%